Examining the Factors Influencing Environmental Innovations - Massimiliano Mazzanti; Roberto Zoboli (Fondazione Eni Enrico Mattei (FEEM), 2006)
Technological innovation is a key factor for achieving a better environmental performance of firms and the economy as a whole, to the extent that it helps to increase the material/energy efficiency of production processes and to reduce emission/effluents associated to outputs. Environmental innovation may spur from exogenous driving forces, like policy intervention, and/or from endogenous factors associated to firm market and management strategies. Despite the crucial importance of research in this field, empirical evidence at firm microeconomic level, for various reasons, is still scarce. Microeconomic-based analysis is needed in order to assess what forces are lying behind environmental innovation at the level of the firm, where innovative practices emerge and are adopted. The paper exploits information deriving from two surveys conducted on a sample of manufacturing firms in Emilia Romagna region -Northern Italy- in 2002 and 2004, located in a district-intense local production system. New evidence is provided by testing a set of hypotheses, concerning the influence of: (i) firm structural variables; (ii) environmental R&D; (iii) environmental policy pressure and regulatory costs; (iv) past firm performances; (v) networking activities, (vi) other non-environmental techno-organizational innovations and (vii) quality/nature of industrial relations. We estimate input and output-based environmental innovation reduced form specifications in order to test the set of hypotheses. The applied investigation shows that environmental innovation drivers, both at input and output level, are found within exogenous factors and endogenous elements concerning the firm and its activities/strategies within and outside its natural boundaries. In the present case study, the usual structural characteristics of the firm and performances appear to matter less than R&D, induced costs, networking, organisational flatness and innovative oriented industrial relations. Environmental Policies and environmental voluntary auditing schemes exert some relevant direct and indirect effects on innovation, although evidence is mixed and further research is particularly needed. Although this new empirical evidence is focussing on a specific industrial territory, we provide food for discussion on firm environmental innovation strategies, and research suggestions for further empirical work.
Keywords: C21; L60; O13; O30; Q20; Q58; 330; Environmental innovation; Environmental R&D; Manufacturing sector; Local system; Environmental policy; Networking; Umweltmanagement; Innovation; Forschung; Verarbeitendes Gewerbe; Emilia-Romagna